Parate Executie dalam Fidusia Menurut Ratio Decidendi Putusan Mahkamah Konstitusi - Rumawi Rumawi; Udiyo Basuki; Mellisa Towadi; Supianto Supianto (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
This article aims to analyze legal subjects whose rights have been violated by the Fiduciaire Act. The Act law can be revoked by the Constitutional Court. The act that violates the rights of subjects is the rule in the provisions of parate executie on Fiduciaire Act. The first analysis is the ontology of parate executives that inflict certain subjects, and the second analysis is the ratio decidendi decision of the Constitutional Court Number 18/PUU-XVII/2019. This paper uses dogmatize analysis. The decisions of the Constitutional Court are analyzed with the doctrine of experts and regulations. Parate execution is a right attached to the recipient fiduciary which can exercise if the fiduciary giver breaks the commitment. Collateral is auctioned through a public offering submitted by the recipient of guarantee. Default by a fiduciary giver occurs if there is an agreement between the giver and the fiduciary recipient. Default occurs based on legal remedies in determining the default. The agreement of the collector with the fiduciary acquirer, the emergence of a broken pledge experienced by the fiduciary giver can give birth to a parate executie.